The ornamentation of rural grounds - Smith, Phoebe (My University, 1897)
Introduction: The art of ornamenting home grounds has now reached a state of perfection not attained by any of the ancients—it is a modern exercise of taste and result of civilization. Though it has been growing in America ever since the country was taken possession of by the English, it was not until recent years that it has made any marked progress. The American people inherited an ardent love for rural life and its pursuits from their English ancestors; but being placed in a new country little time, until lately, was found to cultivate a taste for rural embellishment. However we are a home loving people and he who loves his home will assemble about it the comforts and elegancies of life which not only increase his own enjoyments, but strengthens his patriotism and makes him a better citizen. Professional talent is seldom employed in this art because almost everyone fancies himself able to plan and arrange his own residence, and certainly he is capable of so doing if he has a practical knowledge of the few principles and suggestions that can be given, together with good judgment and common sense.
Citation: Smith, Phoebe. The ornamentation of rural grounds. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Horticulture; Landscaping; Theses; Manuscripts (documents)